Art deco textiles - Samuels, Charlotte (London V&A Publications, 2003)
Art Deco Textiles' provides a visual record of the fabrics which clothed the smart women and furnished the stylish interiors of Europe and America between the years 1910-1939.
Keywords: Textile design -- History -- 20th century; Textile design -- Exhibitions; Art deco